Automation in Hydrographic Survey – The Hydraut Solution - Sluiter, P. G. (The International Hydrographic Review, 2015)
General aspects are treated, to aid in the decision making process for the introduction of automation in hydrography. Partial automation of only one or several of the tasks of data logging, computing, plotting, survey preparation and navigation may be preferable. Design of an optimal system requires close cooperation by experts in automation and hydrography. Flexibility is of extreme importance so that a basic — and relatively cheap — system can be gradually extended to grow with an organisation’s need for more sophistication. The article concludes with the example of a configuration of the Hydraut system, designed by Applied Dynamics Europe and in use by the Dutch Hydrographic Service.